MECHANISMS FOR IMPLEMENTING GOOD GOVERNANCE IN THE MEMBER STATES OF THE EUROPEAN UNION - Telychkan , Yuriy (Theory and Practice of Public Administration, 2020)
The mechanisms of good governance in the EU Member States are analyzed in the article. It is found that the implementation of Good Governance in the EU Member States is determined by the Strategy for Innovation and Good Governance. The Strategy was adopted by the Committee of Ministers of the Council of Europe on March 26, 2008 and aims to improve local governance based on a joint commitment of governments, associations of local authorities and individual local authorities. The Strategy provides for a comprehensive definition of good democratic governance under the 12 Principles and establishes a mechanism for implementation on the basis of: the commitments of individual local authorities to continuously improve their activities with respect to the 12 Principles (adoption and regular monitoring); national action programs agreed between the government and the associations of local authorities; Good Democratic Governance Badge; a Council of Europe body composed of all stakeholders (Stakeholder Platform). The implementation of the Strategy depends on the efforts of national (and / or regional) authorities, associations of local authorities and, ultimately, individual local authorities. It should also be noted that the need to improve local governance is recognized by all European countries, and it is clear that ways and means of doing so may vary from region to region. In some countries there is an urgent need for further decentralization, while in others decentralization may reach an optimum level. In some countries, central government may play a key role in the implementation of the Strategy, in others it may be almost entirely within the scope of the associations (local governments). In some countries, tools for improving local governance, such as capacity building, performance management and teaching methods in others, may already be very sophisticated and widespread, while in other countries they may be at very early stages.